Assessment of Complete Blood Counts of Cannabis sativa Smokers in Ekpoma, Edo State, Nigeria - R. A. Amaechi; I. O. Babatope; P. O. Abulele; B. N. Obodo (Archives of Current Research International, 2020)
Smoking of Cannabis sativa (Marijuana), a known psychoactive substance may result in side effect on living cells of the system. The aim of this study is to assess the complete blood count of Cannabis sativa smokers and make comparison with non-smokers in Ekpoma, Edo State. A total of one hundred subjects were recruited for this study which consist of Fifty (50) Cannabis sativa smokers and fifty (50) non Smokers which served as control. A complete record of medical and smoking history was obtained for each subject, with the use of the questionnaire. The samples obtained were taken to the laboratory for analysis using Sysmex KX auto analyzer. The result showed that the levels of WBC, RBC, granulocytes, lymphocytes, monocytes, Haemoglobin, packed cell volume and platelet levels were significantly lower (p<0.05) in cannabis smokers as compared to the control. The MCV, MCH, MCHC, RDW, PDW and MPV values of cannabis smokers were significantly different (p<0.05) as compared to the control subjects. In conclusion, this study showed that haematological parameters of cannabis smokers differed significantly from non-smokers.